Back Cover: Development of Continuous Flow Systems to Access Secondary Amines Through Previously Incompatible Biocatalytic Cascades (Angew. Chem. Int. Ed. 34/2021). Issue 34 (21st June 2021) - Mattey, Ashley P.; Ford, Grayson J.; Citoler, Joan; Baldwin, Christopher; Marshall, James R.; Palmer, Ryan B.; Thompson, Matthew; Turner, Nicholas J.; Cosgrove, Sebastian C.; Flitsch, Sabine L.
Abstract : Compartmentalised flow reactors allow biocatalytic cascades that would be impossible using standard methods, as described by Sebastian C. Cosgrove, Sabine L. Flitsch, and co‐workers in their Research Article on page 18660 . Carbonyl intermediates were continuously generated via biocatalytic oxidation, then converted into different amine products using immobilised aminating enzymes. The use of flow equipment allowed exquisite control of the paths and enabled a range of new biocatalytic cascades to be constructed, paving the way for fully automated continuous biocatalytic cascades.